TiO2 paste for DSSC photoanode: preparation and optimization of application method - I. O. Selyanin (Uralʹskij federalʹnyj universitet imeni pervogo Prezidenta Rossii B.N. Elʹcina, 2020)
We propose a simple method of TiO2 paste preparation from titania powder (Degussa) and organic binders (terpineol, ethyl cellulose) for making a continuous photoactive layer of a dye-sensitized solar cell (DSSC). The prepared paste was characterized by using thermogravimetric and X-ray diffraction methods for comparison with commercial paste (Solaronix). The TiO2 layer parameters for applying and annealing were optimized by varying the layer thickness and using different masks. The surface morphology of annealed layers was controlled by optical microscopy. Before TiO2 paste applying and after annealing, the conductive glass (fluorine-tin oxide – FTO) was treated by TiCl4 hydrochloric acid solution. The structure of DSSCs were composed FTO-glass / TiO2 layer sensitized Ruthenium complex (N719 dye)/ iodide-based electrolyte / Pt counter electrode/ FTO glass. The DSSC photovoltaic characteristics were measured under AM 1.5G irradiation and demonstrated to be close to those of photoanodes based on the prepared and commercial pastes.